Root system of Panicum maximum Jacq. cv. IPR-86 Mil(e)over-capnio fertilized with nitrogen and submitted to rotational stocking - Sarmento, Patricia; Rodrigues, Luis Roberto de Andrade [UNESP]; Lugao, Simony Marta Bernardo; da Cruz, Mara Cristina Pessoa [UNESP]; de Campos, Fabio Prudencio; Ferreira, Manoel Evaristo [UNESP]; de Oliveira, Ricardo Ferraz (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2008)
The effect of nitrogen on the root system of the species Panicum maximum Jacq. cv. IPR-86 Mil (e) over cap nio, under grazing, was evaluated. The N rates were 0; 150; 300 and 450 kg/ha. year. The root density was evaluated during pregrazing at five years of successive N application, in three depths (0-10; 10-20 and 20-40 cm) and the root growth at 7, 14, 21, and 35 days after grazing. The grazing method adopted was rotational stocking. Root length and root mass densities in pre-and post-grazing presented maximum values at rates 204, 206, 192, and 197 kg/ha of N, respectively. The root growth (in root length density) increased, on average, until 29 days after grazing at rates 0, 150, and 300 kg/ha; at 450 kg/ha N rate, the increase was linear. Independently of N rates, around 60 and 25% of IPR-86 Mil (e) over cap nio cultivar root system was concentrated in 0-10 and 10-20 cm depth, respectively.
Keywords: Grass; Pasture; root density